Economia circular e reciclagem de plásticos: análise das barreiras tecnológicas e regulatórias da pirólise no Brasil - Franchi, Natália Serio (Universidade Federal de São Carlos, 2025)
Brazil, with a population exceeding 200 million inhabitants, has established itself as the world's fourth-largest generator of plastic waste, facing a critical scenario marked by one of the planet's lowest effective recycling rates, with only 1.28% utilization in contrast to the global average of 9%, an inefficiency that is aggravated by the limited coverage and performance of selective waste collection, which encompasses a mere 5.9% of the total volume of residential waste. In light of this environmental and social problem, the present work aimed to analyze the technological and regulatory barriers that impede the full implementation of the Circular Economy in the management of plastic waste in the country, with a particular focus on the prospects for advancement through chemical recycling, using pyrolysis as the main case study. The methodology employed was qualitative and exploratory, based on a systematic review of specialized literature, combined with an in-depth documentary analysis of Brazilian public policies, notably the National Solid Waste Policy (PNRS), in comparison with relevant international regulatory frameworks, in addition to an economic, technological, and regulatory assessment of the pyrolysis process. The results compiled comparative economic analysis data and outlined the main obstacles imposed by the aforementioned barriers, allowing the study to identify and propose concrete suggestions to generate a positive and significant impact on plastic waste management, aligned with the principles of the Circular Economy. The research demonstrated that pyrolysis represents a superior alternative to mechanical recycling for the treatment of complex plastics in the Brazilian context, being capable of promoting circularity by converting these materials into oils, gases, and char. However, despite the high economic viability of the process, which is intrinsically linked to operation at large scales (above 1000 kg/h), the most prominent barrier to the consolidation of the technology lies in the regulatory gap that prevents the recognition of pyrolysis oil as a high-value recycled raw material. To unlock the potential of this technology in Brazil, it is concluded that a dual approach is indispensable, harmonizing the essential regulatory recognition of pyrolysis oil with the optimization of the operational scale through Chemical Engineering.
Circular economy and plastics recycling: an analysis of the technological and regulatory barriers to pyrolysis in Brazil
Keywords: Economia circular; Reciclagem de plásticos; Pirólise; Barreiras tecnológicas; Barreiras regulatórias; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; 12. Consumo e Produção Responsáveis